The ladies of El Cid: The rise of the female voice. (XXI Century. Spanish Literature and Culture, 2008)
The utilization of a real character of the past as a point of departure in the moment of creating a novel of the so-called ¨historical¨ genre, is very frequent and beneficial in the literary actuality and Spanish editorial.  This study analizes the female characters that surround El Cid in the works: Doña Jimena Díaz de Vivar.  Gran señora de todos los deberes (1960) by María Teresa León, Anillos para una dama (1973) by Antonio Gala y Urraca (1982) by Lourdes Ortiz, to show how agency of the feminine voice close to the figure of Rodrigo Díaz de Vivar grows and becomes more determined as socio-political conditions change in the twentieth century.  This work presents how these novels radically depart from the etiquette of historical novel by using the same discourse of national myth of the Re-conquest under which they live in order to minimize it and reconstruct it from a different point of view from that of the classic phallocentric Cid: the feminine.
Keywords: femal characters; feminism criticism; history